Evaluación de desempeño de distintos software para la generación de ortofotomosaicos a partir de imágenes multiespectrales tomadas con un vehículo aéreo no tripulado (2018)
This work shows the application of photogrammetric processes from field work in Chingaza National Natural Park with the recording of multispectral aerial photographs captured by an Unmanned Aerial Vehicle and the recording of data from ground control points, to office work with processing of images for the reconstruction of three-dimensional geometry of the scene, georeferencing, generation of Digital Surface Models and finally ortophotomosaics. This is done through the use of different software, both conventional and aimed at Unmanned Aerial Vehicles, in order to compare results such as geometric precision and visual quality, and intrinsic factors such as cost, ease of use and processing time.